2006
DOI: 10.1111/j.1365-2249.2006.03257.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and curcumin suppress immune response through CD28/CTLA-4 and CD80 co-stimulatory pathway

Abstract: SummaryThe role of resveratrol and curcumin is well documented in cancer, inflammation, diabetes and various other diseases. However, their immunosuppressive action on T cells, B cells and macrophages is not well documented. In the present study, we have ascertained the effect of resveratrol and curcumin on T and B cells and macrophages. The most striking findings were that both resveratrol and curcumin suppressed the activity of T and B cells and macrophages, as evidenced by significant inhibition in prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 24 publications
7
93
0
2
Order By: Relevance
“…Gaddipati et al (2003) reported that curcumin treatment suppresses the production of IL-10 mRNA at 2 and 24 h after hemorrhage/resuscitation and this action is mediated through the inhibition of NF-kB activation and activation of protein-1 (AP-1). On the other hand, other studies reported that curcumin enhances the expression of IL-10 mRNA in different cell lines (Grandjean-Laquerriere et al, 2002;Sharma et al, 2007). Our result comes in accord with the previous study of Zhang et al (2006) whom stated that curcumin treatment of chronic colitis led to an increase in the expression of IL-10 mRNA in colon mucosa but could not increases the level of IL-10 in serum.…”
Section: Discussionsupporting
confidence: 92%
“…Gaddipati et al (2003) reported that curcumin treatment suppresses the production of IL-10 mRNA at 2 and 24 h after hemorrhage/resuscitation and this action is mediated through the inhibition of NF-kB activation and activation of protein-1 (AP-1). On the other hand, other studies reported that curcumin enhances the expression of IL-10 mRNA in different cell lines (Grandjean-Laquerriere et al, 2002;Sharma et al, 2007). Our result comes in accord with the previous study of Zhang et al (2006) whom stated that curcumin treatment of chronic colitis led to an increase in the expression of IL-10 mRNA in colon mucosa but could not increases the level of IL-10 in serum.…”
Section: Discussionsupporting
confidence: 92%
“…This could be due to the different experimental systems. However, in agreement with our data, curcumin had been shown to enhance IL-10 production by human T cells and mouse macrophages [48,49]. Furthermore, curcumin inhibition of NF-kB was dependent on IL-10, in that curcumin failed to inhibit NF-kB activity in IL-10 À/À mice [50].…”
Section: Discussionsupporting
confidence: 90%
“…Resveratrol was reported to reduce the production of prostaglandin E2 (PGE2) and the formation of ROS in lipopolysaccharide (LPS)-activated microglial cells [53,54]. Moreover, resveratrol was reported to suppress the activity of T-and B-cells, and macrophages [55]. Singh et al [56] showed that resveratrol induced both caspasedependent and caspase-independent apoptosis in activated T-cells in experimental allergic encephalomyelitis-induced mice.…”
Section: Other Health Benefits Of Resveratrolmentioning
confidence: 99%